PENGARUH TEKNIK PEMODELAN BERBASIS PENDEKATAN SAINTIFIK TERHADAP KETERAMPILAN MENULIS TEKS BIOGRAFI SISWA KELAS X SMAN 3 BUKITTINGGI - Septia, Melly; Abdurahman, Abdurahman; Tamsin, Andria Catri (Universitas Negeri Padang, 2018)
ABSTRACTÂ The purpose of this research there are three. First, to mendeskripsi and explain the level of writing skills text about a student of class X of SMAN 3 Bukittinggi before applying the scientific approach based modeling techniques. Second, to mendeskripsi and explain the level of writing skills text about a student of class X of SMAN 3 Bukittinggi after applying the scientific approach based modeling techniques. Third, to analyze the effect the application of the technique of modeling-based scientific approach towards writing skills text about a student of class X of SMAN 3 Bukittinggi. Type of this research is quantitative research with experimental methods. The draft study was One Group Pretest and Posttest Design. The population in this research is the grade X SMAN 3 Bukittinggi listed year lessons 2017/2018 as many as 238 people. The sample in this study as many as 34 students that are defined by using purposive sampling technique. The research of the variable is a text biography writing skills using the technique of modeling-based scientific approach. The results of the research there are three, i.e. as follows. First, the text of the biography writing skills before using engineering modeling based approach to saintifk grade X SMAN 3 Bukittinggi is at more than enough qualifications (LdC) with an average of 66.62. Second, the skills of writing the text of the biographies after using the technique of modeling scientific-based approach students class X SMAN 3 Bukittinggi is at Good qualifications (B) with an average of 78.83. Third, based on the t-test, the alternative hypothesis (H_1) received on the standard of 95% and significant degrees of freedom (dk) = (n_1 n_2 +)-2, ttabel > thitung because IE 9.07 > 1.70.Â Kata kunci: teknik pemodelan berbasis pendekatan saintifik, teks biografi, SMAN 3 BukittinggiÂ